Enhancing clinical reasoning skills through tailored CPC in pathology laboratory instruction - Li, Shanshan; Tan, Xufei; Fang, Jie; Dong, Jingyin (Frontiers in Medicine, 2025)
BackgroundIn medical education, fostering students’ clinical reasoning skills is crucial for assessing their clinical proficiency. However, developing a Clinical Pathological Conference (CPC) model tailored to the unique needs of early-stage learners remains an intriguing avenue for exploration.MethodsThis study aimed to enhance the clinical reasoning and critical thinking abilities of early-stage medical students in pathology laboratory instruction through the introduction of a customized CPC teaching method. A total of 279 undergraduate students from the clinical medicine program at Hangzhou City University participated in the study. The 2021 cohort (n = 139) received traditional teaching methods, while the 2022 cohort (n = 140) was taught using a reformed CPC case-based approach. Evaluations included post-class case analysis scores, final examination scores, overall evaluation scores, and an online survey to assess feedback on teaching content, student engagement, and learning outcomes.ResultsStudents who underwent the CPC case teaching method exhibited higher levels of enthusiasm, participation, learning efficiency, and clinical reasoning abilities compared to those following traditional teaching methods. Quantitative results also showed improvements in post-class case analysis and final examination scores. Qualitative feedback indicated that the method was generally well-received, although some students suggested improvements in group collaboration and personalized guidance.ConclusionThe course-specific CPC teaching method effectively enhances students’ learning enthusiasm, classroom participation, learning efficiency, and clinical thinking abilities in pathology laboratory instruction. These findings pave the way for future research to explore the design and implementation of CPC methods in other foundational medical courses and to evaluate their effectiveness.